THE DIFFERENTIAL AGRANULOSIT OF BALI CATTLE BASED ON ORGANIC MAINTENANCE - Swari, Ni Kadek Rahayu; Suwiti, Ni Ketut (Buletin Veteriner Udayana, 2022)
The research has been done to find out the differential cells of lymphocyte and monocytes of Bali cattle with organic based maintenance. Whole blood samples from 10 bali cattle were taken through a jugular vein and were made of blood vessel preparations and stained with Harris Hematoxsilin-Eosin. The data were collected by calculating lymphocyte and monocyte cells by cross-sectional method which was examined using binoculars 100X magnification microscope. The results showed, the average percentage of lymphocytes obtained was 55.2% and monocytes were 7.8%. The value is still in the normal value of lymphocytes and monocytes in cattle.